SISTEM SORTIR PAKET OTOMATIS DENGAN CONVEYOR DAN KAMERA ESP32-CAM - Hadi Prasetyo, Yosafat; Ixbal, Lifandi; Berkat Gea, Utema; Dwisaputra, Indra; Fitri Arriyani, Yang (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2025)
The manual package sorting process in the shipping industry is time-consuming and prone to errors. This study aims to design and build an automatic package sorting system to improve efficiency and accuracy. The design method used is VDI 2222 which includes the stages of analysis, conceptualization, design, and completion. The system utilizes a conveyor as a package transfer path, ESP32‑CAM with OCR to read area codes, ultrasonic sensors to detect package presence, and servo motors as guide actuators. The test results show that ESP32‑CAM successfully reads area codes such as “SGL‑B‑06”, “SGL‑B‑07”, and “SGL‑B‑08” accurately; the ultrasonic sensor has an average deviation of 0.32cm; and the entire series completes sorting in less than 30 seconds per package. The implementation of this tool has been proven to optimize the sorting process, minimize manual intervention, and increase the speed and accuracy of package separation based on destination.